Pengenalan Teater sebagai Bentuk Literasi terhadap Alam bagi Warga Ponggok (Klaten) - Ari Jogaiswara Adipurwawidjana; Lestari Manggong; Mega Subekti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
The workshop activity outlined in this article is an introduction to theater with the topic of the body and its relevance to water empowerment for the citizens of Ponggok (Klaten) and surrounding areas. The workshop was motivated by a reaction to the need to titrate Ponggok residents to conserve natural resources in their villages. The provision of a medium for Ponggok Village residents in particular and GLC19 festival participants in general to be able to understand the importance of community survival water can help them experience an understanding of the sustainability of Ponggok Village's natural resources. The method used is to provide an introduction to the body's exercise in relation to respect for the existence and function of water in life. The activity was carried out on one occasion, in two stages: (1) an introduction to theater and theater functions for character education and introduction to the natural surroundings, and (2) the practice of theatrical approach through bodybuilding movements by empowering water. The result obtained is that this medium creates a creative space for participants to instill the values ​​of understanding about the importance of water through theater approach.